End-Point Information Security in the Healthcare Industry: A Critical Review - Uzzaman, Arif; ., . (International Journal of Engineering and Technology, 2018)
The ability of the healthcare industry to keep abreast with the evolving trends in endpoint information security depends on combinations of measures. In the current literature, some of these measures include the development of analytics capable of spotting intruders on time, embracing quick reactions to potential or detected intrusions, and the decision to employ robust system defenses. In this paper, the main aim was to review the current literature regarding the subject of endpoint information security, with critical insights gained from the case of the healthcare industry. Findings suggest that the healthcare industry forms one of the most attractive arenas for security attackers. Some of the healthcare organizations that have been victims of recent security attacks include the Californian Hollywood Presbyterian Medical Center that experienced a data breach in February 2016 and MedStar Health Inc. (in the same month). In the following month, San Diegoâ€™s Alvaro Hospital Medical Center was also targeted for cyber attack. Hence, some algorithms have been proposed to counter these attacks; including the use of SOA-based EHRs, the implementation of the RBAC model, the use of k-anonymity, k-unlinkability, and the SQL searching mechanisms that target the patientsâ€™ encrypted data. Also, some strategies have been proposed as best practices in endpoint information security. These strategies include the management of identity lifecycles, the establishment of risk-aware cultures, the management of third-party security compliance, and securing healthcare firmsâ€™ devices in terms of design. Overall, it is evident that the complexity of endpoint information security in the healthcare industry (due to the evolution of applications such as virtualization and cloud computing) implies that the ability to survive from future security attacks will depend on the firmsâ€™ ability to keep abreast with industry demands.Â